The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.48550/arxiv.1703.00485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A review of two decades of correlations, hierarchies, networks and clustering in financial markets

Gautier Marti,
Frank Nielsen,
Mikołaj Bińkowski
et al.

Abstract: We review the state of the art of clustering financial time series and the study of their correlations alongside other interaction networks. The aim of the review is to gather in one place the relevant material from different fields, e.g. machine learning, econophysics, statistical physics, econometrics, behavioral finance. We hope it will help researchers to use more effectively this alternative modeling of the financial time series. Decision makers may also be able to leverage its insights. Finally, we also … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 198 publications
(305 reference statements)
0
21
0
Order By: Relevance
“…Many large scale systems are best described as networks [3,4,5,12,20,33,31,41]. A standard approach of network construction is to create covariance-based measures of interlinkages [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many large scale systems are best described as networks [3,4,5,12,20,33,31,41]. A standard approach of network construction is to create covariance-based measures of interlinkages [41].…”
Section: Discussionmentioning
confidence: 99%
“…A co-movement network is constructed by considering each response variable as a node of the graph and an undirected edge between two nodes exists if the corresponding correlation is nonzero. This kind of network construction out of observational multi-variate data has been very successful as a modeling paradigm in finance [31] and biology [12,3] among others. However, such inference about existence of linkages from purely observational data has a problem.…”
Section: Introductionmentioning
confidence: 99%
“…About the same time, Mantegna, another econophysicist, discovered the hierarchical structure of financial correlations [15] whose seminal and influential work sparked a rich empirical research in financial networks and clustering. An extensive review of this literature can be found in [16].…”
Section: Financial Correlation Matricesmentioning
confidence: 99%
“…Other authors have also followed up on and expanded this work by studying graph dynamics over time [3,20] and examined methods for building the graph [5,21,19]. In fact, to this day, the topic of graphs as a model for equity markets remains a subject of discussion in the literature [1,23].…”
Section: Previous Workmentioning
confidence: 99%